Restriction and enhancement of human immunodeficiency virus type 1 replication by modulation of intracellular deoxynucleoside triphosphate pools. - Meyerhans, A (1994)
Human immunodeficiency virus type 1 (HIV-1) replication is shown to be sensitive to the intracellular concentration of deoxynucleoside triphosphate substrates. Addition of thymidine to established cell lines resulted in a dramatic reduction of virus production. The effect could be substantially alleviated by addition of deoxycytidine, which, alone, enhanced viral titers by a factor of 2 to 3. Hydroxyurea treatment abolished HIV-1 replication in peripheral blood mononuclear cells and could be reversed by deoxyadenosine. These data show that HIV-1 replication occurs under suboptimal DNA precursor conditions.